1994
DOI: 10.1007/bf00194612
|View full text |Cite
|
Sign up to set email alerts
|

Glycosylation pattern and enzyme activities in atrophic, angulated skeletal muscle fibres from ageing rats

Abstract: In this study enzyme activities and lectin binding patterns in skeletal muscle from very old rats were investigated in order to evaluate changes in enzyme activity or carbohydrate expression in senile muscle. Activities for adenosine triphosphatase (ATPase), succinic dehydrogenase, non-specific esterase and the binding pattern for 31 lectins were investigated in the soleus muscles from very old (36 months) and young (3 months) rats. In ageing muscles atrophic, angulated muscle fibres are frequent. In cryostat … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

1996
1996
2010
2010

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 38 publications
0
3
0
Order By: Relevance
“…Kirkeby and colleagues (1997) investigated preferential accumulation of complex‐type oligosaccharides recognized by Datura stramonium agglutinin in type IIa muscle fibers. In another study, comparison of skeletal muscles from old and young rats showed preferential cytoplasmic binding of seven lectins to the angulated aging fibers (Kirkeby,1994). …”
Section: Discussionmentioning
confidence: 97%
“…Kirkeby and colleagues (1997) investigated preferential accumulation of complex‐type oligosaccharides recognized by Datura stramonium agglutinin in type IIa muscle fibers. In another study, comparison of skeletal muscles from old and young rats showed preferential cytoplasmic binding of seven lectins to the angulated aging fibers (Kirkeby,1994). …”
Section: Discussionmentioning
confidence: 97%
“…10 By contrast, few data have been reported on the effects of advanced age. [11][12][13] Alterations in GS activity were demonstrated with advanced age (Ͼ22 months 14 ). GS activity was increased by a factor of 1.5-to 2-fold in 25-27-month rats and may be a consequence of aging-induced stress.…”
mentioning
confidence: 96%
“…for anal vaccination (Pajak and Danguy, 1993). tion in the expression of sarcoplasmic glycoconjugates is also involved in atrophic skeletal myocytes from ageing rats (Kirkeby, 1994).…”
Section: Glycan Expression In Skeletal Musclementioning
confidence: 99%